2016
DOI: 10.18632/oncotarget.11260
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of homeobox gene Barx2 increases gastric cancer proliferation and metastasis and predicts poor patient outcomes

Abstract: Barx2 is a Bar family homeodomain transcription factor shown to play a critical role in cell adhesion and cytoskeleton remodeling, key processes in carcinogenesis and metastasis. Using quantitative real-time PCR, Western blotting, and immunohistochemistry, we found that Barx2 is expressed at lower levels in human gastric cancer (GC) tissues than in adjacent normal mucosa. In a multivariate analysis, Barx2 expression emerged as an independent prognostic factor for disease-free and overall survival. Kaplan-Meier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 46 publications
3
26
1
Order By: Relevance
“…A previous study revealed that Barx2 inhibited gastric cancer cell proliferation and invasiveness through inhibition of the Wnt/β‐catenin signaling pathway . In the present study, Barx2 overexpressing cells (A549‐pBarx2) reduced nuclear β‐catenin, c‐MYC, and HIF‐1α expression (Fig a).…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…A previous study revealed that Barx2 inhibited gastric cancer cell proliferation and invasiveness through inhibition of the Wnt/β‐catenin signaling pathway . In the present study, Barx2 overexpressing cells (A549‐pBarx2) reduced nuclear β‐catenin, c‐MYC, and HIF‐1α expression (Fig a).…”
Section: Resultssupporting
confidence: 69%
“…β‐Catenin, as a central downstream effector of Wnt signaling, plays a critical role in the regulation of tumor growth and development . Because Barx2 has been reported to be involved in Wnt signaling, we explored the effect of Barx2 on the Wnt/β‐catenin signaling pathway in NSCLC carcinogenesis . Our results reveal that Barx2 inhibits Wnt/β‐catenin signaling in NSCLC cells.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…BARX2 encodes a homeobox transcription factor that can function as a tumor suppressor and its down regulation is a predictor of poor prognosis in different cancer types [20][21][22] . BARX2 can bind the estrogen receptor (the target of tamoxifen) and influence estrogen-dependent growth and cellular invasion 23 .…”
Section: Discussionmentioning
confidence: 99%